The idea of archive in the modern work of art - Frickmann, Daniel; Felix da Costa, Carlos Eduardo (Revista do Colóquio, 2020)
Based on texts that present the methods and conceptual principles of a modern artist, the article seeks to understand the conditions for registering a work of art and the creation of art as a record of ourselves. Being the modern artist a creator of works with aesthetic potential located in industrial society between the 19th and 20th centuries, the purpose of this reflection is to conceive an idea of archive within the perspectives and procedural decisions of modern art. The reason for this is to understand how art is used as archival production and is archived.